FcÎ³ receptor III expression and morphological maturity on neutrophil are associated with higher iron level of major beta-thalassemia - Ghozali, Mohammad; Cakranita, Tiwi Harjanti; Tjahjadi, Adi Imam; Reniarti, Lelani; Ghrahani, Reni; Syamsunarno, MRAA; Setiabudiawan, Budi; Panigoro, Ramdan (Cellular and Molecular Biology, 2018)
Lifetime blood transfusion experienced by major Î²-thalassemia patients complicated with iron overload, therefore, may lead to their tissue injury. Ultimately, free toxic iron may alter immune response via dysregulation of immune cell activity producing prolonged effector reaction. Neutrophil as one of the vital innate immune cell despite serves as the first line of defense resulting acute inflammation has a pivotal role in chronic inflammation while releasing the toxic substance that interferes biological processes. This process is initiated by one of them by activation of FcÎ³ Receptor III (CD16), a neutrophil membrane-bound protein. A cross-sectional laboratory study involving lysed-erythrocyte heparinized whole blood of fifty pediatric major Î²-thalassemia patients treated with monoclonal antibodies i.e. CD16, CD14, and HLA-DR, dissected into CD16+ and CD16++ population using flow cytometry. Expression of FcÎ³ Receptor III was measured as Median Fluorescent Intensity (MFI). Hematology and iron status were measured. A correlation analysis was done. MFI of CD16 neutrophil [509.5 (371 – 796.5)] and ferritin level [(3209 µg/L, 1862 – 4564)] was positively correlated (r = 0.4, P = 0.007). Respectively, ferritin and serum iron were found negatively correlated with segmented neutrophils (r = -0.3, P = 0.02; r = -0.3, P = 0.02). Change in CD16 expression may implicate preliminarily neutrophil activation as a response of iron-overloaded tissue and result in chronic inflammation in Î²-thalassemia patients. However, the maturity of this cell may be altered.  Future study in the understanding of neutrophil-mediated inflammation, particularly related to immune complexes and functionality, is imperative to be explored.